The Relationship between Injury History and the Risk of Sports Injuries at Arema Football Academy U-18 - Abror, Muhammad Ulil; Prastowo, Bayu; Irawan, Dimas Sondang; Anwar, M. Choirul (Department of Physical Education, Sport, Health and Recreation, 2024)
Football players generally have good physical conditions, such as strength, endurance, explosive power, speed, balance, flexibility, coordination, agility, accuracy and power. This does not rule out the possibility of a risk of sports injury because football players are one of the highest contributors to sports injuries compared to other sports, namely 32%. Factors causing the risk of sports injuries can be due to age, BMI, playing technique, physical condition, body posture, warming up, wrong accessories, forces coming from opponents or other athletes, and training intensity that is too heavy, as well as having history of previous injury. Injuries often experienced by football players include bruises, abrasions, muscle cramps, strains, sprains and fractures. Aims to determine the relationship between injury history and the risk of sports injuries at Arema Football Academy U-18. This research uses analytical observational methods with a cross-sectional study design, the population and sample of this study were Arema Football Academy U-18 athletes. Data were collected using the FMS and OSTRC-H questionnaires. FMS is used to determine the risk of injury, while OSTRC-H is used to determine injury history. Based on the research results, it shows that the normality test value is P= 0.000 (<0.005) so that the data is not normally distributed and then uses the correlation test with the Spearman correlation test. From the results of the Spearman correlation test, it was found that P= 0.000 (<0.05), so Hо was rejected and H₁ was accepted, and the value r= -0.615 was also obtained, which means the relationship is strong and has a negative value. These results can be interpreted statistically as there is a relationship between injury history and the risk of sports injuries at the Arema Football Academy U-18.